Prophetic Communication in Tafsir Al-Mishbah: Tabshir–Indzar, Hiwar, and Amtsal as A Model of Transcendental Communication - Febi Yushari; Muhammad Syahrial Razali Ibrahim (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
This study examines prophetic communication in the Qur’an through the interpretive framework of Tafsir Al-Mishbah by Muhammad Quraish Shihab and maps its major communicative strategies into a persuasive-dialogic model relevant to contemporary da'wah. The study employs a qualitative library research design with Tafsir Al-Mishbah as the primary source, supported by relevant scholarship in Qur’anic exegesis, Islamic communication, and contemporary religious communication. The unit of analysis consists of Quraish Shihab’s interpretive constructions of selected Qur’anic verses that reflect the communicative dimensions of prophethood. The analysis was conducted through thematic interpretation (tafsir mawḍū‘ī), close reading, thematic coding, and conceptual interpretation using persuasive, dialogic, and transcendental communication frameworks. The findings show that prophetic communication in Tafsir Al-Mishbah is structured through several interconnected strategies, namely tabshīr (encouragement and glad tidings), indzār (warning and moral caution), ḥiwār (dialogical engagement), and amtsāl (parable-based communication). These strategies are further guided by ethical principles such as ḥikmah, mau‘izhah ḥasanah, gentleness, and participatory engagement. The study concludes that prophetic communication in Tafsir Al-Mishbah constitutes a coherent model of transcendental communication that integrates persuasion, dialogue, symbolic teaching, and ethical responsibility.